2010
DOI: 10.1021/bc1003789
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing Activity of siRNA Polyplexes Based on Thiolated N,N,N-Trimethylated Chitosan

Abstract: N,N,N-Trimethylated chitosan (TMC) is a biodegradable polymer emerging as a promising nonviral vector for nucleic acid and protein delivery. In the present study, we investigated whether the introduction of thiol groups in TMC enhances the extracellular stability of the complexes based on this polymer and promotes the intracellular release of siRNA. The gene silencing activity and the cellular cytotoxicity of polyplexes based on thiolated TMC were compared with those based on the nonthiolated counterpart and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 47 publications
1
41
1
Order By: Relevance
“…Hence, optimal mass or N/P ratio should not only refer to transfection efficiency, but also to a satisfactory toxicity feature. On the other hand, increasing chitosan concentration relative to that of siRNA implies increased mass or N/P ratio, which has been demonstrated to be accompanied by a decrease in particle size, probably the increased polymer amount leads to tighter complexes [16,81,[89][90][91]. In other words, increasing siRNA concentration decreases this ratio, resulting in increased particle size which may be due to increased siRNA bond-forming bridges between chitosan chains, consequently leading to greater chitosan incorporation [65].…”
Section: Effect Of Mass or N/p Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, optimal mass or N/P ratio should not only refer to transfection efficiency, but also to a satisfactory toxicity feature. On the other hand, increasing chitosan concentration relative to that of siRNA implies increased mass or N/P ratio, which has been demonstrated to be accompanied by a decrease in particle size, probably the increased polymer amount leads to tighter complexes [16,81,[89][90][91]. In other words, increasing siRNA concentration decreases this ratio, resulting in increased particle size which may be due to increased siRNA bond-forming bridges between chitosan chains, consequently leading to greater chitosan incorporation [65].…”
Section: Effect Of Mass or N/p Ratiomentioning
confidence: 99%
“…Furthermore, the use of these derivatives is expected to potentiate in vivo transfection kinetics with respect to both efficiency and sustained gene silencing. To this end, structural modifications of chitosan have been explored, such as quaternization of the amine group [27,91] and the introduction of functional groups [82,91] as well as conjugation with other polymers [78] or ligands [78,106]. In this regard, chitosan derivatization has been shown to create safer and more efficient gene vectors [78].…”
Section: Nanocarrier-based Sirna Delivery Using Chitosan Derivativesmentioning
confidence: 99%
“…Adding histidine (pK a~6 ) residues to chitosan further improved buffering capacity and overall transfection efficiency (Chang et al, 2010). Recently, it was also shown that the introduction of thiol groups in N,N,N-trimethylated chitosan improved its efficiency as a siRNA carrier (Varkouhi et al, 2010). Red blood cells (RBC) were used for the delivery of macromolecules before liposomes became popular.…”
Section: Non-viral Vectorsmentioning
confidence: 99%
“…Moreover, it was found that disulfide bonds increased the stability of the nanoparticles under high salt conditions. 90 Xiao et al 91 developed new oral nanoparticle systems, TNF-α siRNA-loaded Man-modified cationic polymeric nanoparticles (TPP-PPM/TNF-α siRNA NPs), for IBD treatment. The B-PEI (25 kDa) was connected to the end group of cystamine bisacrylamide (CBA) via a Michael addition reaction.…”
mentioning
confidence: 99%